Trump's Trade Offensive and The Gulf Response: Navigating a New Era of US-Middle East Economic Relation - Fadhlia, Maudy Noor; Fahlevi, Zhillan Zhalila (Journal Of Middle East and Islamic Studies, 2025)
In 2025, the Trump administration implemented sweeping tariff measures as part of its "America First" trade agenda. While aimed broadly at correcting trade imbalances, these policies have had significant ripple effects on Middle Eastern economies, particularly in the Gulf. The objective is to examine how the Trump administration’s tariff regime constitutes a deliberate exercise in economic statecraft and how Gulf states are responding to preserve economic sovereignty and geopolitical relevance. The methodology involves qualitative research method and collecting the data through documents. The paper distinguishes the U.S. tariff regime through the lens of economic coercion, categorizing these tariffs as strategic maneuvers rather than mere economic adjustments. The results show Gulf states responded with financial market adjustments, export disruptions, and accelerated economic diversification, regional alliances, and hedging strategies. This redefines U.S.–Middle East economic relations, with Gulf states increasingly asserting strategic autonomy amid shifting global power dynamics. The article concludes by assessing the broader geopolitical implications of this evolving trade confrontation for future U.S. engagement in the region.